The Paradox of Regulation: Why Emotion Management Increases Climate Anxiety in Generation Z - Handayani, Anndiny Anastasya; Jaroah, Siti (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Abstract: Climate change is the defining existential crisis of the 21st century, posing a unique psychological burden on Generation Z. While emotion regulation (ER) typically buffers against clinical anxiety, its role in the context of global environmental threats remains contested. This study examines the relationship between ER and climate anxiety among Gen Z (N = 411), investigating gender as a potential moderator. Contrary to established psychological paradigms where regulation reduces distress, our results reveal that higher emotion regulation significantly amplifies climate change anxiety. This suggests that in the face of systemic environmental collapse, "effective" regulation does not function as a sedative; instead, it may heighten emotional proximity and sensitivity to ecological threats. Furthermore, gender significantly moderates this relationship, indicating distinct pathways of emotional processing between groups. These findings challenge the traditional definition of "adaptive" regulation, suggesting that for Gen Z, climate anxiety may be a rational, regulated response rather than a pathology. We propose a shift in psychological interventions from symptom reduction to "distress integration" for climate resilience. Keywords: Climate Anxiety, Gen Z, Regulation Emotion